A prototype tool of optimal wireless sensor placement for structural health monitoring - Shi, W.; Wu, Changzhi; Wang, X. (2018)
© Springer International Publishing AG, part of Springer Nature 2018. With increasing collapses of civil infrastructures and popularized utilization of large-scale structures, worldwide deployment of structural health monitoring (SHM) systems is of importance in emerging and future SHM industry. A reliable and practical tool of optimal wireless sensor placement (OWSP) can promote implementation of wireless-based SHM systems by reducing construction cost, extending lifetime and improving detection accuracy. This paper presents a prototype of wireless sensor placement (WSP) for bridge SHM based on multi-objective optimisation (MOO) technique and bridge information modelling (BrIM) technology. MOO technique is used to determine sensor locations by simultaneously searching for multiple trade-offs among structural engineering, wireless engineering and construction management. The BrIM model will be used as a platform to validate and visualize the proposed MOO. A BrIM integrated design tool will be developed to improve the efficiency in design stage through visualisation capabilities and semantic enrichment of a bridge model. As future applications, 4D BrIM that combines time-related information in visual environments with the 3D geometric and semantic BrIM model will help engineers and contractors to visualise possible defects and project costs in the real world.